Lodging Recommendations Using the SparkML Engine ALS and Surprise SVD - Ramadhan, Sageri Fikri; Baizal, Z K Abdurahman; Rismala, Rita (STMIK Budi Darma, 2020)
Recommendation system is a process or tool used to provide predictions for users to choose something based on an existing domain. This system has become a primary need for today's modern digital industry such as in the entertainment, shopping, and service sectors. In this research, we focus on how to develop a recommendation system for accommodation services. We use the Alternating Least Square and Singular Value Decomposition methods to predict and recommend lodging to users